2023
DOI: 10.12659/aot.939149
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dietary Quality and Serum Cystatin C in Kidney Transplant Recipients Based on Chinese Diet Balance Index 2016 (DBI-16)

Abstract: Background Cystatin C (Cys) is considered to be a better marker than serum creatinine in assessing kidney function, predicting cardiovascular events, and all-cause mortality. It seems to be associated with nutritional status in the general population, but little is known about kidney transplant recipients (KTRs). This study aimed to explore the relationship between dietary balance index and serum Cys in KTRs. Material/Methods In a cross-sectional study, 215 KTRs complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…It is suggested that this is related to the nutritional status of the general population. For example, Zhang et al (2023) [29] assessed that greater consumption of dairy products and meat and a greater variety of diet were associated with lower levels of CysC.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that this is related to the nutritional status of the general population. For example, Zhang et al (2023) [29] assessed that greater consumption of dairy products and meat and a greater variety of diet were associated with lower levels of CysC.…”
Section: Discussionmentioning
confidence: 99%
“…In determining the sample size for our predictive model, our study employed a data-driven approach, utilizing existing datasets to establish the requisite sample size. Drawing from Kendall's prescription, advocating that studies elucidating factors of in uence require a sample size encompassing 5 to 10 times the number of variables, we navigated a total of 16 variables within this study [21]. Computed through the criterion of a sample size ampli cation of 10 times the number of variables, our analysis mandated no fewer than 160 patients for comprehensive coverage.…”
Section: Sample Sizementioning
confidence: 99%